A remarkable legion of guests: Diversity and host specificity of army ant symbionts. Issue 20 (18th August 2021) - von Beeren, Christoph; Blüthgen, Nico; Hoenle, Philipp O.; Pohl, Sebastian; Brückner, Adrian; Tishechkin, Alexey K.; Maruyama, Munetoshi; Brown, Brian V.; Hash, John M.; Hall, W. E.; Kronauer, Daniel J. C.
Abstract: Tropical rainforests are among the most diverse biomes on Earth. While species inventories are far from complete for any tropical rainforest, even less is known about the intricate species interactions that form the basis of these ecological communities. One fascinating but poorly studied example are the symbiotic associations between army ants and their rich assemblages of parasitic arthropod guests. Hundreds of these guests, or myrmecophiles, have been taxonomically described. However, because previous work has mainly been based on haphazard collections from disjunct populations, it remains challenging to define species boundaries. We therefore know little about the species richness, abundance and host specificity of most guests in any given population, which is crucial to understand co‐evolutionary and ecological dynamics. Here, we report a quantitative community survey of myrmecophiles parasitizing the six sympatric Eciton army ant species in a Costa Rican rainforest. Combining DNA barcoding with morphological identification of over 2, 000 specimens, we discovered 62 species, including 49 beetles, 11 flies, one millipede and one silverfish. At least 14 of these species were new to science. Ecological network analysis revealed a clear signal of host partitioning, and each Eciton species was host to both specialists and generalists. These varying degrees in host specificities translated into a moderate level of network specificity, highlighting the system's level of biotic pluralism in terms of biodiversity and interaction diversity. By providing vouchered DNA barcodes for army ant guest species, this study provides a baseline for future work on co‐evolutionary and ecological dynamics in these species‐rich host–symbiont networks across the Neotropical realm.